FINANCIAL PERFORMANCE ANALYSIS BEFORE AND AFTER THE ACQUISITION OF GO PUBLIC COMPANIES (CASE STUDY AT PT. DIAN SWASTIKA SENTOSA Tbk 2018 – 2020) - Sudarmi - - (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2022)
The purpose of this study was to determine the financial performance before and after the acquisition. The financial performance is measured through financial ratios using the analysis of the current ratio, debt equity ratio, total asset turnover, return on equity, and earnings per share. The type of research used is descriptive quantitative. The data analysis method used in this study is the Wilcoxon's signed rank test. The results of the Wilcoxon's signed rank test showed that all variables in the 2 years before and 5 years after the acquisition had an Asymp.Sig (2-tailed) value greater than the predetermined significance value (> 0.05). Where the variable current ratio, return on equity, debt equity ratio, earnings per share has an Asymp.Sig value of 0.180 and the total asset turnover variable has a value of 0.655. The company's financial performance did not experience a significant difference before and after the acquisition.